Qualitative and quantitative image analysis of CT and MR imaging in patients with neuroendocrine liver metastases in comparison to 68Ga-DOTATOC PET - Flechsig, Paul; Zechmann, Christian; Schreiweis, Julian; Kratochwil, Clemens; Rath, Daniel; Schwartz, Lawrence H.; Schlemmer, Heinz-Peter; Kauczor, Hans-Ulrich; Haberkorn, Uwe; Giesel, Frederik L. (European journal of radiology, 2015)
Purpose - To compare lesion conspicuity in patients with liver metastases arising from gastroenteropancreatic neuroendocrine tumors (GEP-NETs) using MRI, PET and CT. - Materials and methods - 16 patients with GEP-NETs were evaluated using non-contrast MRI, contrast-enhanced (CE) MRI using Gd-EOB-DTPA and CE-68Ga-DOTATOC PET. Quantitative analyses were performed by two blinded readers using ROI-analyses quantifying contrast ratios (CR) between normal liver-tissue and GEP-NET-metastases. Qualitative analyses were performed evaluating primary visibility and spatial detectability of all lesions. - Results - 103 of the same liver metastases were detected on all modalities. Qualitatively, lesion conspicuity was superior on CE-MRI imaging compared to non-contrast MR-sequences (T2, DWI, fl2D, fl3D), as well as arterial- and portal-venous phase CT. Concerning detectability of lesions, CE-MRI was superior to all other modalities. The quantitative ROI-analysis demonstrated improved CR for DWI compared to all other non-contrast MR-sequences (p<0.001). CE-MRI presented with higher CR-values compared to CE-68Ga-DOTATOC PET/CT (p<0.001). - Conclusions - Anatomic imaging using non contrast MRI with fl2D-and fl3D-sequences in combination with the molecular imaging modality 68Ga-DOTATOC PET is optimal for the assessment of liver lesions in GEP-NET-patients. Even though CE-MRI was superior to non-contrast MRI, non-contrast MRI is sufficient to detect and quantify liver metastases in daily routine, especially in combination with DW-Imaging.